“Una libidine di saggezza”: Amelia Rosselli’s Documento - Peterson, Thomas (Quaderni d'Italianistica, 2023)
This study of Amelia Rosselli’s third major collection follows the chronological order of the poems’ composition, clarifying the poet’s intentions to embark on a path that privileges internal objectivity and communication. Careful attention is paid to the derivation from Petrarch and medieval Italian love poetry. The love theme is tied to a spiritual problematic evident in the book’s extensive use of sacred and Christological imagery. This finds the subject in often ambiguous situations of tension and trial that nevertheless express her goal of freedom in defense of the dignity of the person. This religious-philosophical vein is likened to the current of personalism that emerged in France and Europe in the years of Rosselli’s formation.